2021
DOI: 10.1007/s00167-021-06738-x
|View full text |Cite
|
Sign up to set email alerts
|

Full thickness quadriceps tendon grafts with bone had similar material properties to bone-patellar tendon-bone and a four-strand semitendinosus grafts: a biomechanical study

Abstract: Purpose Despite increasing interest in utilizing quadriceps tendon (QT) grafts in anterior cruciate ligament reconstruction (ACLR), data on the optimal quadriceps graft thickness are limited. The purpose of this study was to characterize the mechanical properties for the quadriceps tendon, comparing full-thickness (FT) QT grafts with and without bone to a partialthickness (PT) QT graft, and comparing the three QT grafts to four-stranded semitendinosus (4-SST) and bone-patellar tendon-bone (BTB) grafts and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
(60 reference statements)
0
17
0
1
Order By: Relevance
“…The ultimate load to failure of BPTB autograft ranges from 319 to 4389 N, with the highest load reported in 15 mm-wide grafts [ 75 ]. In clinical practice, 10 mm-wide grafts with ultimate loads to failure of 1880 to 2664 N are typically used [ 26 , 50 , 111 ].…”
Section: Biomechanicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ultimate load to failure of BPTB autograft ranges from 319 to 4389 N, with the highest load reported in 15 mm-wide grafts [ 75 ]. In clinical practice, 10 mm-wide grafts with ultimate loads to failure of 1880 to 2664 N are typically used [ 26 , 50 , 111 ].…”
Section: Biomechanicsmentioning
confidence: 99%
“…Similarly, the ultimate load to failure for a 10 to 12 mm-wide QT autograft ranges from 249 to 2186 N [ 50 , 75 , 111 ]. QT autograft with bone block, as well as full-thickness grafts appear to have higher ultimate loads to failure compared to all-soft tissue or partial thickness grafts [ 111 ].…”
Section: Biomechanicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A biomechanical study has shown equivalent material properties to the hamstrings and patellar tendons, regarding strength and volume. 9 Second, the graft is predictable in length and diameter, which is not the case with patellar tendon and hamstrings. 5 Third, there is less postoperative weakness in ACL agonists than after harvesting of hamstring tendons, with low donor side morbidity.…”
Section: Video Transcriptmentioning
confidence: 99%